Peanut Productivity Under The Albizia Stand With Agroforestry System In Community Forest, Magetan East Java Indonesia - Susanto, Anang; M Winarni; Parwi (Publisher Cv. Inara, 2021)
An effort to meet the national food need is by utilizing productive forest areas under albizia stands. Food stuff such as peanuts can grow under albizia forest stands. The purpose of this research was to know success of agroforestry system implemented to tree after initial release of contract. This study was conducted under albizia stand of state forest Magetan in East Java. Research design was used in this study was randomized block design. 5- year- old albizia stages with 0%, 25%, 50 % trimming intensity with plant spacing of 3 m x 4 m, Albizia trees that used for this comparison as many as 90 albizia trees. Results showed that soil lies under 5-year-old albizia trees still produced peanut with highest weights 129 g/m and lowest weight 117 g/m2 while highest biomass about 115.10 g and lowest biomass about 98.23 g. Application of agroforestry system under 5-year-old albizia stand is still good and intensive, creating work, improving social welfare, local community opinion change into positive perceptions for forestry development, forest protection, forest fire prevention, reducing rapid forest degradation and environmental quality conservation of forest areas.